PERAN PEMERINTAH DALAM PENGELOLAAN TEMPAT PEMAKAMAN UMUM (TPU) TAMPAN JALAN UKA KECAMATAN TAMPAN KOTA PEKANBARU - Rahmat Hidayat; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The government role of management TPU Tampan Uka Street Tampan District, Pekanbaru City. This research was conducted at Tampan TPU Tampan District, Pekanbaru City. The purpose of this study is to determine the implementation of the government's role in managing TPU Tampan and government obstacles in carrying out the role of managing Tampan TPU. In conducting the research, the determination of the subject was carried out using purposive sampling technique whose criteria had been determined based on the needs of this study, these criteria based, 7 informants were taken as research subjects. The theory used in this research is the role theory by Soerjono Soekanto. The results of this proposed research are that the informants as the Coordinator of the TPU, TPU and Community officers explained that the role of the government as a regulator has been going well. Meanwhile, the government's role as a dynamist is also running well and the role of the government as a facilitator is going well too. The obstacle in the management of this Tampan TPU is the absence of electricity, which causes the work of TPU officers to be hampered, such as it is difficult to turn on the water machine for their needs.Keyword: Role, Government, TPU Tampan.